Efforts to Improve Teacher Professional Competence in Preparing HOTS Questions Through Workshop Techniques at SDN 22 Mataram - Liswati Liswati; Usman Jayadi; Riinawati R (International Journal of Education and Digital Learning (IJEDL), 2022)
The background of this research is the lack of teacher ability in planning, compiling and presenting HOTS (High Order Thinking Skill) questions to students at Mataram 22 Public Elementary School. This certainly has an impact on the low ability of students in analyzing questions with high-level thinking skills or solving HOTS-level questions which results in low scores on student learning outcomes. Efforts to increase the ability to compose HOTS questions are carried out by completing 10 (ten) elements of HOTS item preparation including analyzing Basic Competencies and Indicators, making question level distributions, determining operational verbs, making question grids, creating questions, creating stimuli, determining variations of questions, make distribution of answer keys, make scoring guidelines, make a review of the questions and analyze the validity of the questions. The data collected is data in the form of planning documents for preparing HOTS questions as well as the activities of teachers and students in developing critical thinking skills. Based on the analysis of the data obtained into 77 HOTS questions preparation documents and HOTS-based teaching and learning activities that have been carried out, the result is that there has been an increase in the teacher's HOTS questions preparation ability from pre-cycle activities 63% to 72% in cycle I and increased again to 85 % in cycle II. In addition, the increase in teaching and learning activities according to the level of high-level thinking (HOTS) compiled by the teacher also increased from an average of 71.00 to 77.00 in cycle I and increased to 84.00 in cycle II. Based on the data obtained.